Comparative evaluation of black currant subzone of the taiga of the Komi Republic - O. K. Timusheva; V. N. Sorokopudov (Овощи России, 2023)
Relevance. Black currant (Ribes nigrum L.) occupies an important place in amateur gardening of the Komi Republic as an economically valuable crop. There is no doubt that it is possible and necessary to develop berry growing in the Komi Republic, to meet the needs of the population in multivitamin products through local production of berries. The purpose of the paper was to study the economically useful traits of varieties cultivated in the North in the conditions of the middle subzone of the taiga. Winter hardiness, phenological phases, productivity, large-fruitedness (berry weight), biochemical composition of berries were analyzed.Methodology. The results of the study of six varieties of black currant in 2020–2022 are presented. Plants are nine to ten years old. The research was carried out according to the "Program and methodology for the study of variety of fruit, berry and nut crops" (1999). Currants are planted in rows according to the scheme 4 x 1.5.Results. As a result of the research, it was revealed that the studied varieties of black currant are promising for cultivation in the middle subzone of the taiga. In all studied varieties, vegetation was observed in the second-third decade of April. The beginning of flowering was observed in the middle of the second – the end of the third decade of May, 25–39 days after the beginning of the growing season. The beginning of fruit ripening was noted in the first-second decades of July, 48-52 days after the start of the flowering. Mass ripening of berries was noted in the middle of the second – the end of the third decade of July, and the middle of the second-first decade of August for “Lazy” variety. During the study period, the vegetation of black currant ended in the second decade of October, with the onset of temperatures below 5°C. The duration of the vegetation period over the years of research was above the norm and equaled 169-185 days. The productivity of black currant varieties was 1.16-1.79 kg per bush. All varieties are characterized by large fruits (berries) weighing 1.02-1.66 g. A biochemical analysis of frozen berries of blackcurrant varieties for 2021-2022 was carried out regarding the content of ascorbic acid, sugars, acidity, solids. The maximum content of ascorbic acid was noted in “Vologda” variety – 97.68 mg%. The highest sugar-acid index was in “Bagira” variety – 3.5. All the varieties have a high content of dry matter in berries: 18.04-20.38%. Overall, the varieties of black currant under study suit for cultivation in the middle subzone of the taiga.